Fabrication of an antiferroelectric NaNbO3-CaZrO3 film on a (001)SrTiO3 substrate by pulsed laser deposition. (21st August 2019) - Beppu, Kosuke; Iida, Yosuke; Adachi, Hideaki; Fujii, Ichiro; Wada, Takahiro
Abstract: The present study demonstrates the antiferroelectric property of a 0.94NaNbO3 -0.06CaZrO3 thin-film deposited on a SrRuO3 coated (001)SrTiO3 single crystal substrate fabricated by a pulsed laser deposition method. X-ray diffraction reciprocal space mapping and electron diffraction patterns show that the crystal structure of the 0.94NaNbO3 -0.06CaZrO3 thin film has a fourfold super lattice structure of antiferroelectric NaNbO3 . The 0.94NaNbO3 -0.06CaZrO3 thin film shows an antiferroelectric double polarization–electric field ( P–E ) hysteresis loop. The hysteresis of the P–E response became clear with rising measurement temperature. Furthermore, the 0.94NaNbO3 -0.06CaZrO3 thin film exhibits antiferroelectrc behavior at a high temperature of 160 °C.